In vitro Prebiotic Properties of Garlic Polysaccharides and Its Oligosaccharide Mixtures Obtained by Acid Hydrolysis - Lu, Xiaoming; Li, Ningyang; Zhao, Renjie; Zhao, Meng; Cui, Xuanxuan; Xu, Yukun; Qiao, Xuguang (Frontiers in Nutrition, 2021)
Fructans and oligofructose are usually used as prebiotics without any limitation in functional food or food ingredients. The degree of polymerization (DP) of polysaccharides affects the utilization of probiotics. Garlic is rich in fructans. The objective of this study was to extract and purify polysaccharides from garlic, analyze its composition, hydrolyze them using HCl, and then evaluate the prebiotic potential of the garlic neutral polysaccharides (GPs) before and after hydrolysis. GPs were 6.57 × 103 Da with a composition of fructose and glucose at a ratio of 4:1. After acid hydrolysis, low molecular weight fraction in garlic oligofructose (GOs) may be eliminated through ultrafiltration. The content of oligosaccharides with an average DP < 10 increased from 15 to 75%. GPs and GOS had a stronger resistance to acid conditions in human stomach than fructooligosaccharide, and GOs showed better prebiotic properties on the growth of lactobacilli than GPs. This study evaluates the prebiotic potential of the garlic frutctans and oligosaccharides mixtures obtained by acid hydrolysis, which may be used as an ingredient in functional food and nutraceutical products.